Efektivitas Psikoedukasi Visual dan Partisipatif dalam Meningkatkan Pemahaman Anti-Bullying pada Siswa Sekolah Dasar - Jafar, Eka Sufartianinsih; R, Riandra Maghfira; Lathifah, Andhini Dinda; Maharani, Zohraya; Utami, Andi Anisa Mutia (DEDIKASI, 2025)
Abstract. This study aims to examine the effectiveness of visual and participatory psychoeducation themed "Stop Bullying: We Are All Valuable" in improving students' understanding of bullying in SD X. This study used a quasi-experimental method with a one group pre-test and post-test design. A total of 30 grade 3 students participated in this program. After the pre-test, students participated in psychoeducation through posters, videos, and interactive games. The normality test results showed that the data were normally distributed, and the paired samples t-test analysis results showed a significant difference between the pre-test and post-test scores with a significance value of p = 0.000 (p < 0.05). The mean score of the post-test was higher than the pre-test, indicating that students' understanding improved after participating in the psychoeducation. Thus, this visual and participatory psychoeducation is effective to increase students' awareness about bullying and can be a preventive effort in creating a safe school environment for students. Keywords: bullying, psychoeducation, elementary school students, visual, participatory.